HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENGETAHUAN IBU TENTANG TUMBUH KEMBANG ANAK BALITA DI SRAGEN - Ambarwati, Retno; Ratnasari, Nita Yunianti; Purwandari, Kristiana Puji (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
An important period in child development is the toddler period. In this toddler the development of language skills, creativity, social awareness, emotional and intelligence goes very fast and is the cornerstone of subsequent developments. Problems of growth and development of children under the age of five (Toddler) in life are things that `must be known and studied by a mother. Monitoring the growth and development of infants is one of the important activities to find out the obstacles in growth (growth faltering) early. Mother's education is one of the important factors in child development. Mother's education is good, so she can receive all information from outside, especially about how to take good care of children and maintain good children's health.The Objective of this research is to analyze the relationship between mother's education level and the level of mother's knowledge about the growth and development of children under five in Anna Sragen Kindergarten. This research is observational with cross sectional approach. The research subjects were 20 respondents. Sampling with a simple random sampling system. Data on maternal education was obtained from the results of questionnaires and knowledge of mothers through questionnaires. Data analysis using Chi-Square test. The results of the test of the relationship between the level of education with the level of knowledge of mothers about the growth and development of children under five shows the value of p = 0.013 (p <0.05). The OR value from the above results shows that mothers with low education levels are more at risk of having less knowledge about child development and development of toddlers by 16.3 times compared to mothers who have high education levels (OR = 16,349). There is a significant relationship between the level of mother's education with the level of mother's knowledge about the growth and development of children under five.